Distributed Attack Detection For Wireless Sensor Networks - Annamalai Giri, A.; Mohan, E. (International Journal of Engineering and Technology, 2018)
Wireless sensor network when data are transmitting between devices may cyber attackers interfere and try to hack the data,Â Â In order to avoid attackers we are proposing fusion center monitoring, which finding the attackers and communicating theÂ Â information to cluster head. Through cooperative detection method fusion head is alarming the neighbor nodes to avoid theÂ Â congestion. This proposed methodology is enhanced prevent the deduction for attack in wireless sensor networks.Â Â Â